COVID-19 and Its Association with New-Onset Diabetes - Ajmera, Kunal M. (Archives of Clinical and Medical Case Reports, 2021)
Since the beginning of 2020, people’s lives have been changed worldwide as a result of the ongoing coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Research shows a bidirectional association between COVID- 19 infection and diabetes mellitus. Whether COVID-19 causes new-onset diabetes in those at or without risk is unclear. More data are needed to explore the possible role of SARS-CoV-2 in new-onset diabetes post-infection. Here, the case of a young otherwise healthy patient is described; the patient presented with signs and symptoms of new-onset diabetes requiring insulin and was diagnosed with COVID- 19 at the same time.